Output-Feedback Control of Virus Spreading in Complex Networks With Quarantine - Alarcón-Ramos, Luis A.; Bernal Jaquez, Roberto; Schaum, Alexander (Frontiers in Applied Mathematics and Statistics, 2018)
In this paper the problem of designing an output-feedback control for the stabilization of the extinction steady-state in a virus spreading process over a complex network with quarantine is considered. Sufficient conditions are established for the choice of those nodes for which sensor information is necessary and those which should be controlled using notions from constructive control theory. A simple output-feedback control is proposed which exponentially stabilizes the extinction state. Numerical simulation results are provided to illustrate the functioning of the proposed control scheme for a scale-free network of one million nodes.